Поцелуй дьявола: роман / Барбара Картленд - Картленд Барбара (Очарование, 2006)
Экземпляры: ф.1 (20160421) / Инвентарный номер: 40245 / Цена: 35.00 / Авт.знак: К 271 / ГРНТИ: 17.82.31 / ББК: 84 (4 Вел)